Efeito da inoculação de probiótico in ovo sobre a morfometria intestinal e controle de salmonella enteritidis - Martins, Bruna Boaro [UNESP] (2015)
A trial was conducted to evaluate broiler performance, intestinal biometric parameters, carcass and commercial cuts yield. Day-old male Cobb® chicks (720; stocking density 12 birds/m2) were allotted to one of three treatments (T1, T2 and T3; eight replications per treatment; 30 birds per pen) in a completely randomized design. Chicks were vaccinated in ovo against Marek's disease on day 18 of incubation (T1, control), inoculated in ovo with probiotics diluted in Marek's disease vaccine on day 18 of incubation (T2), or vaccinated in ovo against Marek's disease on day 18 of incubation and sprayed with probiotic solution at hatching (T3). Weight gain, feed intake, feed conversion rate (FCR) and livability were evaluated at 7, 21, 35 and 42 days of age; production efficiency factor was determined at the end of the rearing period. Intestinal biometric analysis (15 birds per treatment; 45 birds per slaughter) was performed at hatching and at 7, 21, 35 and 42 days of age; 42 day-old birds (25 birds per treatment) were randomly selected for carcass yield determination. Data were analyzed using analysis of variance and means compared using the Tukey test at a 5% significance level. In the pre-starter phase, birds submitted to T2 had significantly higher FCR than birds submitted to T3, but similar FCR to birds submitted to T1 (control). At 21 days of age, birds submitted to T2 or T3 had significantly longer jejunal segments than birds submitted to T1 (control). Probiotic inoculation in ovo improved feed conversion rates in the first week of life and affected intestinal biometric parameters at 21 days of age. Probiotic treatment had no impact on carcass or commercial cuts yield.